Analisis Pengaruh Work Environment, Pay Satisfaction, Job Stress terhadap Employee Performance (Studi pada Pramugari dan Pramugara Low Cost Carrier di Indonesia) - Edi Komara; Andreas Dimas Panji Kusumo (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2018)
This research aimed to identify the influence of work environment, pay satisfaction, job stress on employee performance study in stewardess and a steward low-cost carrier in Indonesia. Data collection using questionnaire by election sample as many as 130 respondents stewardess and a steward who is already working 2 years. This research has a variable exogenous; work environment, pay satisfaction, and job stress, while the endogenous variable is employee performance. This research using analysis Structural Equation Modeling (SEM) withs the methods a descriptive analysis quantitative and the questionnaire as the main data. 26 indicators were used in the study questions by using a scale Likert 1-6 with 21 AMOS tools. It can be concluded that the results are; 1) work environment proven have a positive impact on employee performance. 2) pay satisfaction proven have a positive impact on employee performance. 3) job stress proven have a negative influence on employee performance